FM-NL-coated CFM cathode film and preparation method and application thereof

By using FM-NL@CFM cathode membrane and Ni-CAT@LDH@MWCNT catalyst in microbial fuel cells, the problem of low efficiency in traditional microbial fuel cells when dealing with low-concentration rare earth wastewater is solved, and efficient rare earth element removal and battery performance improvement are achieved.

CN119797510AInactive Publication Date: 2025-04-11LIAONING UNIVERSITY OF PETROLEUM AND CHEMICAL TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510009920.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional microbial fuel cells are inefficient when treating low-concentration rare earth wastewater and cannot completely treat rare earth wastewater, resulting in high treatment efficiency and cost.

Method used

The FM-NL@CFM cathode film is used as the cathode electrode, and the Ni-CAT@LDH@MWCNT catalyst is used to provide more reduction sites for rare earth elements during the electrocatalytic reduction process, thereby improving the reduction efficiency of rare earth elements on the electrode surface.

Benefits of technology

It significantly improves the power generation capacity of microbial fuel cells, improves the electron transfer rate, alleviates membrane pollution, extends the operating time, and achieves efficient removal of rare earth elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797510A_ABST
    Figure CN119797510A_ABST
Patent Text Reader

Abstract

The invention provides an FM-NL-CFM cathode film and a preparation method and application thereof, and belongs to the technical field of wastewater treatment. According to the FM-NL-coated CFM cathode film, dimethylformamide is used as a solvent, polyvinylpyrrolidone is used as a pore forming agent, polyvinylidene fluoride is used as a binder, a Ni-CAT-coated LDH-coated MWCNT catalyst and a substrate are combined, then a phase inversion method is used for curing film preparation, and soaking is carried out in a diluted hydrochloric acid solution and a potassium permanganate solution to prepare the FM-NL-coated CFM cathode film. The prepared FM-NL-CFM cathode membrane can be installed in a membrane assembly to be applied to an MFC, the electricity generation capacity of the MFC can be remarkably improved, the electron transfer rate is increased, the membrane pollution phenomenon is relieved, the operation time is prolonged, rare earth elements are degraded on the surface of the membrane, and efficient removal of the rare earth elements is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wastewater treatment, and in particular relates to a FM-NL@CFM cathode membrane and a preparation method and application thereof. Background Art

[0002] There are many methods currently used for rare earth wastewater treatment, including electrodialysis, chemical precipitation, etc. However, these methods have problems such as low removal rate and high treatment cost, which lead to problems in application. The bioelectrochemical system can convert the chemical energy in the wastewater into electrical energy, which can be used to treat various industrial wastewater and domestic sewage. While achieving efficient sewage treatment, it can generate renewable energy, thereby achieving sustainable use of energy. Therefore, the bioelectrochemical system has broad application prospects.

[0003] Microbial fuel cell (MFC) is a typical bioelectrochemical system, which uses the bioelectrochemical system to decompose the organic matrix in rare earth wastewater and generate bioelectricity, and reduce the metal elements in the rare earth wastewater in the cathode chamber, so as to achieve the purpose of treating low-concentration rare earth wastewater. However, traditional microbial fuel cells still have the problems of low treatment efficiency and incomplete treatment of low-concentration rare earth wastewater. Therefore, it is necessary to explore new microbial fuel cell systems to treat rare earth wastewater. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a FM-NL@CFM cathode membrane and a preparation method and application thereof. The FM-NL@CFM cathode membrane prepared by the present invention can be used as a cathode electrode in a microbial fuel cell to treat low-concentration rare earth wastewater. Compared with the traditional microbial fuel cell cathode, the FM-NL@CFM cathode membrane has the dual functions of electrocatalysis and filtration, which can enable the MFC reaction system to have better effluent water quality performance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A method for preparing a FM-NL@CFM cathode membrane, using dimethylformamide (DMF) as a solvent, polyvinyl pyrrolidone (PVP) as a pore-forming agent, and polyvinylidene fluoride (PVDF) as a binder, combining a Ni-CAT@LDH@MWCNT catalyst with a substrate, and then curing and forming a membrane by a phase inversion method, and then soaking in a dilute hydrochloric acid solution and a potassium permanganate solution to prepare the FM-NL@CFM cathode membrane;

[0008] The Ni-CAT@LDH@MWCNT catalyst is prepared by a mixed hydrothermal reaction of 2,3,6,7,10,11-hexahydroxytriphenyl, nickel acetate and LDH@MWCNT.

[0009] The patent with application number CN202310032551.5 proposes a N-CNT@Fe-Mo catalyst and its preparation method and application. The catalyst can be further prepared to obtain a carbon nanotube-modified magnetic iron catalytic reduction film as a cathode catalytic electrode. Different from the catalytic effect of the N-CNT@Fe-Mo catalyst, the catalytic principle of the Ni-CAT@LDH@MWCNT catalyst of the present invention is: in the MFC reaction system, the addition of the Ni-CAT@LDH@MWCNT catalyst provides more reduction sites for rare earth elements during the electrocatalytic reduction process, which can improve the reduction efficiency of rare earth elements on the electrode surface, thereby improving the electrocatalytic activity of MFC; while the N-CNT@Fe-Mo catalyst reduces rare earth elements through the combined action of electroreduction and electrocoagulation.

[0010] Furthermore, the preparation method of the FM-NL@CFM cathode membrane comprises the following steps:

[0011] Dimethylformamide, polyvinyl pyrrolidone, polyvinylidene fluoride and Ni-CAT@LDH@MWCNT catalyst were mixed and stirred, and reduced iron powder was added, mixed evenly, and degassed to obtain FM-NL@CFM cathode membrane casting solution;

[0012] The FM-NL@CFM cathode membrane casting liquid is coated on a substrate, and after the membrane is formed, it is placed in a dilute hydrochloric acid solution for reaction, and then immersed in a potassium permanganate solution, and then washed with water and dried to obtain the FM-NL@CFM cathode membrane.

[0013] Furthermore, in the FM-NL@CFM cathode membrane casting liquid, the concentration of polyvinyl pyrrolidone is 2wt.%, the concentration of polyvinylidene fluoride is 10wt.%, the concentration of Ni-CAT@LDH@MWCNT catalyst is 0wt.%~1.8wt.%, and the concentration of reduced iron powder is 0wt.%~4wt.%, wherein the concentrations of Ni-CAT@LDH@MWCNT catalyst and reduced iron powder are not 0.

[0014] Furthermore, the concentration of the dilute hydrochloric acid solution is 2 wt.%; and / or

[0015] The concentration of the potassium permanganate solution is 0.2 mol L -1 .

[0016] Furthermore, the substrate is a carbon fiber material, preferably a carbon fiber cloth; and / or

[0017] The soaking time is 12 hours; and / or

[0018] The coating thickness was 300 μm.

[0019] Furthermore, the temperature of the hydrothermal reaction is 120° C. and the time is 12 h.

[0020] Furthermore, the mass ratio of the 2,3,6,7,10,11-hexahydroxytriphenylene, nickel acetate and LDH@MWCN is 7:14:10.

[0021] Furthermore, the LDH@MWCN refers to a composite material of layered double hydroxide (LDH) and mesoporous carbon nanomaterials (MWCN). In a specific embodiment of the present invention, the preparation method of the LDH@MWCN comprises the following steps:

[0022] 0.333 g of cobalt chloride hexahydrate and 0.1426 g of nickel chloride hexahydrate were added into deionized water and stirred evenly. Then 0.2414 g of aluminum chloride hexahydrate and 0.76 g of urea were weighed and added into the above solution and stirred magnetically for 30 min to obtain solution A.

[0023] 0.02 g of multi-walled carbon nanotubes were placed in 60 mL of deionized water and magnetically stirred for 30 min to obtain solution B;

[0024] Solution A and solution B were mixed evenly to obtain solution C, and solution C was subjected to hydrothermal reaction at 140°C for 12 hours. After the reaction was completed, the solution was cooled to room temperature, and the precipitate was collected, washed with deionized water and ethanol respectively, dried in an oven at 60°C, and fully ground to obtain LDH@MWCNT.

[0025] The second technical solution of the present invention:

[0026] A FM-NL@CFM cathode membrane is prepared according to the above preparation method.

[0027] The third technical solution of the present invention:

[0028] A microbial fuel cell uses the FM-NL@CFM cathode membrane as a cathode catalytic electrode.

[0029] The fourth technical solution of the present invention:

[0030] Application of the FM-NL@CFM cathode membrane or the microbial fuel cell in treating rare earth wastewater.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The FM-NL@CFM cathode membrane prepared by the present invention can be installed in a membrane assembly and applied to a microbial fuel cell, and has a significant promoting effect on the redox reaction of the electrode. In the electrocatalytic reduction, the Ni-CAT@LDH@MWCNT catalyst contained in the FM-NL@CFM cathode membrane provides more reduction sites for rare earth elements, and can improve the reduction efficiency of rare earth elements on the electrode surface. Therefore, the FM-NL@CFM cathode membrane is used for the treatment of rare earth wastewater, which can significantly improve the power generation capacity of MFC, increase the electron transfer rate, alleviate membrane pollution and thus prolong the operation time, degrade the rare earth elements on the membrane surface, and realize the efficient removal of rare earth elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 Cyclic voltammograms of the FM-NL@CFM cathode membranes prepared in Examples 1 to 3 and the PVDF@CFM cathode membrane prepared in Comparative Example 1, wherein the abscissa represents voltage (in V), the ordinate represents current (in mA), the scan rate is 10 mV / s, and the temperature is 1 mol L -1 Scanning in sodium sulfate solution;

[0035] Figure 2 This is a graph showing the degradation results of rare earth wastewater by the FM-NL@CFM cathode membrane prepared in Examples 1 to 3 and the PVDF@CFM cathode membrane prepared in Comparative Example 1, wherein the horizontal axis represents time (in h), the vertical axis represents the effluent concentration (in mg / L) and the removal efficiency (in %), and the hollow symbols and solid symbols represent the concentration and removal efficiency of yttrium (Y) ions, respectively. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] The embodiment of the present invention provides a method for preparing a FM-NL@CFM cathode membrane, using dimethylformamide (DMF) as a solvent, polyvinyl pyrrolidone (PVP) as a pore-forming agent, and polyvinylidene fluoride (PVDF) as a binder, combining a Ni-CAT@LDH@MWCNT catalyst with the substrate, and then curing and forming a membrane by a phase inversion method, and then soaking in a dilute hydrochloric acid solution and a potassium permanganate solution to prepare the FM-NL@CFM cathode membrane;

[0042] The Ni-CAT@LDH@MWCNT catalyst is prepared by a mixed hydrothermal reaction of 2,3,6,7,10,11-hexahydroxytriphenyl, nickel acetate and LDH@MWCNT.

[0043] In an embodiment of the present invention, the method for preparing the FM-NL@CFM cathode film comprises the following steps:

[0044] Dimethylformamide, polyvinyl pyrrolidone, polyvinylidene fluoride and Ni-CAT@LDH@MWCNT catalyst were mixed and stirred, and reduced iron powder was added, mixed evenly, and degassed to obtain FM-NL@CFM cathode membrane casting solution;

[0045] The FM-NL@CFM cathode film casting liquid is coated on a substrate, and after the film is formed, it is placed in a dilute hydrochloric acid solution for reaction, and then immersed in a potassium permanganate solution to generate Fe3O4 and MnO2 in the cathode film, and then washed with water and dried to obtain the FM-NL@CFM cathode film.

[0046] Phase inversion curing film is a polymer film preparation technology, and its core principle is to transform the homogeneous film-making liquid into a solid film by changing the phase state of the solution. This method includes thermally induced phase inversion and concentration change processes, wherein the thermally induced phase inversion triggers phase inversion by temperature change, and the concentration change is achieved by evaporating the solvent or adding a non-solvent. The phase inversion film-making process of the present invention comprises DMF solvent, PVP pore former, PVDF binder, Ni-CAT@LDH@MWCNT catalyst and substrate, and the film-forming process is divided into two stages: the first stage is the phase separation process, when the casting liquid is immersed in the coagulation bath, the solvent and the non-solvent will diffuse with each other through the liquid film / coagulation bath interface, resulting in phase separation of the casting liquid; the second stage is the phase inversion process, after the film-making liquid system is phase-separated, the solvent and the non-solvent are further exchanged, and the condensation of the membrane pores, the interphase flow and the polymer-rich phase solidification film formation occur.

[0047] During the phase inversion curing film-making process, the concentration of the polymer in the casting liquid will affect the structure and properties of the membrane, while affecting the phase separation behavior, and further affecting the microstructure of the membrane. Based on this, in a preferred embodiment of the present invention, in the FM-NL@CFM cathode membrane casting liquid, the concentration of polyvinyl pyrrolidone is 2wt.%, the concentration of polyvinylidene fluoride is 10wt.%, the concentration of Ni-CAT@LDH@MWCNT catalyst is 0wt.%~1.8wt.%, and the concentration of reduced iron powder is 0wt.%~4wt.%, wherein the concentrations of the Ni-CAT@LDH@MWCNT catalyst and the reduced iron powder are not 0.

[0048] In a preferred embodiment of the present invention, the concentration of the dilute hydrochloric acid solution is 2 wt.%; and / or

[0049] The concentration of the potassium permanganate solution is 0.2 mol L -1 .

[0050] In a preferred embodiment of the present invention, there is no limit on the amount of the dilute hydrochloric acid solution and the potassium permanganate solution used, as long as the membrane product can be completely immersed.

[0051] In a preferred embodiment of the present invention, the substrate is a carbon fiber material, preferably a carbon fiber cloth; and / or

[0052] The soaking time is 12 hours; and / or

[0053] The coating thickness was 300 μm.

[0054] In a preferred embodiment of the present invention, the temperature of the hydrothermal reaction is 120° C. and the time is 12 hours.

[0055] In a preferred embodiment of the present invention, the mass ratio of 2,3,6,7,10,11-hexahydroxytriphenylene, nickel acetate and LDH@MWCN is 7:14:10.

[0056] The LDH@MWCN used in the embodiment of the present invention refers to a composite material of layered double hydroxide (LDH) and mesoporous carbon nanomaterials (MWCN). In a specific embodiment of the present invention, the preparation method of the LDH@MWCN comprises the following steps:

[0057] 0.333 g of cobalt chloride hexahydrate and 0.1426 g of nickel chloride hexahydrate were added into deionized water and stirred evenly. Then 0.2414 g of aluminum chloride hexahydrate and 0.76 g of urea were weighed and added into the above solution and stirred magnetically for 30 min to obtain solution A.

[0058] 0.02 g of multi-walled carbon nanotubes were placed in 60 mL of deionized water and magnetically stirred for 30 min to obtain solution B;

[0059] Solution A and solution B were mixed evenly to obtain solution C, and solution C was subjected to hydrothermal reaction at 140°C for 12 hours. After the reaction was completed, the solution was cooled to room temperature, and the precipitate was collected, washed with deionized water and ethanol respectively, dried in an oven at 60°C, and fully ground to obtain LDH@MWCNT.

[0060] The embodiment of the present invention provides a FM-NL@CFM cathode membrane, which is prepared according to the above preparation method.

[0061] The embodiment of the present invention provides a microbial fuel cell, using the FM-NL@CFM cathode membrane as a cathode catalytic electrode.

[0062] The room temperature in the embodiments of the present invention refers to 25±2°C.

[0063] All raw materials used in the examples of the present invention are commercially available.

[0064] The technical solution of the present invention is further illustrated by the following embodiments.

[0065] Example 1

[0066] (1) Preparation of LDH@MWCNT

[0067] 0.333 g of cobalt chloride hexahydrate and 0.1426 g of nickel chloride hexahydrate were added into deionized water and stirred evenly. Then 0.2414 g of aluminum chloride hexahydrate and 0.76 g of urea were weighed and added into the above solution and stirred magnetically for 30 min to obtain solution A.

[0068] 0.02 g of multi-walled carbon nanotubes were placed in 60 mL of deionized water and magnetically stirred for 30 min to obtain solution B;

[0069] Solution A and solution B were mixed evenly to obtain solution C, and solution C was subjected to hydrothermal reaction at 140°C for 12 hours. After the reaction was completed, the solution was cooled to room temperature, and the precipitate was collected and washed with deionized water and ethanol respectively, dried in an oven at 60°C, and fully ground to obtain LDH@MWCNT;

[0070] (2) Preparation of Ni-CAT@LDH@MWCNT catalyst

[0071] 105 mg of 2,3,6,7,10,11-hexahydroxytriphenyl was placed in 60 mL of deionized water, and magnetically stirred for 30 min. Then, 210 mg of nickel acetate was added, and ultrasonic treatment was performed at room temperature. Then, 0.15 g of LDH@MWCN prepared in step (1) was added, and magnetic stirring was performed for 30 min to obtain a mixed solution. The mixed solution was hydrothermally reacted at 120° C. for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and the precipitate was collected and washed with deionized water and ethanol respectively. The washed product was dried and ground to obtain a Ni-CAT@LDH@MWCNT catalyst.

[0072] (3) Preparation of FM-NL@CFM cathode membrane casting solution

[0073] 8.22 g of dimethylformamide, 0.2 g of polyvinyl pyrrolidone, 1 g of polyvinylidene fluoride, and 0.18 g of the Ni-CAT@LDH@MWCNT catalyst prepared in step (2) were placed in a beaker and mixed, sealed, and magnetically stirred for 24 h, then 0.4 g of reduced iron powder was added, mechanically stirred for 6 h, and degassed to obtain a FM-NL@CFM cathode film casting solution;

[0074] (4) Preparation of FM-NL@CFM cathode membrane

[0075] Using carbon fiber cloth as the substrate, soak the carbon fiber cloth in a mixed solution of anhydrous ethanol and acetone in a volume ratio of 1:1 for 12 hours, wash it with deionized water for 3 times, dry it, and wipe the coated glass plate and the scraper clean to prevent impurities from entering and affecting the film quality;

[0076] The pretreated carbon fiber cloth was placed on a coated glass plate, and the FM-NL@CFM cathode film casting liquid prepared in step (3) was coated on the surface of the carbon fiber cloth using a scraper. The coating thickness was 300 μm. After the coating was completed, it was left in the air for 40 seconds and immersed for 12 hours. After the film was formed, the prepared cathode film was placed in a 2 wt.% dilute hydrochloric acid solution to react, so that the iron powder was converted into ferrous ions. After repeated rinsing with deionized water, it was placed in 0.2 mol L -1After soaking in potassium permanganate solution for 12 hours, Fe3O4 and MnO2 are generated in the cathode membrane. After the reaction is completed, the cathode membrane is repeatedly rinsed with deionized water to remove unreacted potassium permanganate. After cleaning, the cathode membrane is placed in an electric constant temperature blast drying oven and dried at a constant temperature of 60°C for 2 hours to obtain the FM-NL@CFM cathode membrane, which is cut into a size of 15cm×12cm for standby use.

[0077] Example 2

[0078] The same as Example 1, except that the preparation method of the FM-NL@CFM cathode membrane casting solution in step (3) is different, specifically:

[0079] 8.8 g of dimethylformamide, 0.2 g of polyvinyl pyrrolidone, 1 g of polyvinylidene fluoride, and 0.1 g of the Ni-CAT@LDH@MWCNT catalyst prepared in step (2) were placed in a beaker and mixed, sealed, and magnetically stirred for 24 h, then 0.2 g of reduced iron powder was added, mechanically stirred for 6 h, and degassed to obtain FM-NL@CFM-1 cathode film casting solution;

[0080] The remaining steps are the same as in Example 1.

[0081] The FM-NL@CFM cathode film obtained in this example is recorded as FM-NL@CFM-1 cathode film.

[0082] Example 3

[0083] The same as Example 1, except that the preparation method of the FM-NL@CFM cathode membrane casting solution in step (3) is different, specifically:

[0084] 8.5 g of dimethylformamide, 0.2 g of polyvinyl pyrrolidone, 1 g of polyvinylidene fluoride, and 0.05 g of the Ni-CAT@LDH@MWCNT catalyst prepared in step (2) were placed in a beaker and mixed, sealed, and magnetically stirred for 24 h, then 0.05 g of reduced iron powder was added, mechanically stirred for 6 h, and degassed to obtain FM-NL@CFM-2 cathode film casting solution;

[0085] The remaining steps are the same as in Example 1.

[0086] The FM-NL@CFM cathode membrane obtained in this example is recorded as FM-NL@CFM-2 cathode membrane.

[0087] Comparative Example 1

[0088] Same as Example 1, the only difference is that the casting solution is different, and the specific preparation method is:

[0089] (1) Preparation of PVDF@CFM cathode membrane casting solution

[0090] 8.39 g of dimethylformamide, 0.2 g of polyvinyl pyrrolidone, and 1 g of polyvinylidene fluoride were placed in a beaker, mixed, sealed, and magnetically stirred for 24 h, and then reduced iron powder was added, mechanically stirred for 6 h, and degassed to obtain a PVDF@CFM cathode membrane casting solution;

[0091] (2) Preparation of PVDF@CFM cathode membrane

[0092] Using carbon fiber cloth as the substrate, soak the carbon fiber cloth in a mixed solution of anhydrous ethanol and acetone in a volume ratio of 1:1 for 12 hours, wash it with deionized water for 3 times, dry it, and wipe the coated glass plate and the scraper clean to prevent impurities from entering and affecting the film quality;

[0093] The pretreated carbon fiber cloth was placed on a coated glass plate, and the PVDF@CFM cathode film casting liquid prepared in step (1) was coated on the surface of the carbon fiber cloth using a scraper. After coating, the film was left in the air for 40 seconds, immersed in deionized water for phase inversion, and immersed for 12 hours. After film formation, the cathode film was placed in an electric constant temperature blast drying oven after cleaning, and dried at a constant temperature of 60°C for 2 hours to obtain a PVDF@CFM cathode film, which was cut into a size of 15 cm×12 cm for standby use.

[0094] Performance Testing

[0095] 1. Redox

[0096] The redox properties of the FM-NL@CFM cathode film prepared in Example 1, the FM-NL@CFM-1 cathode film prepared in Example 2, the FM-NL@CFM-2 cathode film prepared in Example 3, and the PVDF@CFM cathode film prepared in Comparative Example 1 were tested by cyclic voltammetry. The scanning speed was set to 10 mV / s at 1 mol L -1 Cyclic voltammetry of FM-NL@CFM was performed in sodium sulfate solution. Figure 1 .Depend on Figure 1 It can be seen that the cyclic voltammetry curve of FM-NL@CFM prepared in Example 1 has an obvious redox peak, indicating that the Ni-CAT@LDH@MWCNT catalyst enhances the catalytic activity of the cathode membrane.

[0097] 2. Performance test of rare earth wastewater treatment

[0098] The structure of the microbial fuel cell (MFC) is mainly composed of an anode chamber, a cathode chamber and a proton exchange membrane (PEM) used to separate the two chambers. The MFC uses an iron nail as the anode. At the same time, the anode chamber is filled with graphite particles and activated carbon particles (filling rate is 90%) inoculated with electricity-producing Shewanella (the strains come from laboratory culture, the main strains are Gammaproteobacteria and Bacteroidia, under anaerobic conditions, they are fed with anhydrous sodium acetate every week, and the specific preparation method is referred to CN202310032551). The FM-NL@CFM cathode membrane of Example 1 is used as the catalytic electrode in the cathode chamber of the MFC. The anode and the cathode are connected with titanium wire, and a suitable resistor is connected externally to form a complete circuit. After the system is assembled, anhydrous sodium acetate is used as a carbon source to provide the organic matter required for the metabolism of the electricity-producing microorganisms themselves. After the MFC system produces electricity stably, prepare a mixture containing 20 mg L -1 The solution of yttrium (Y) ions is used as rare earth wastewater and is directly connected from the cathode to conduct performance tests on the system for treating rare earth elements.

[0099] The PVDF@CFM cathode membrane of Comparative Example 1 was used as the catalytic electrode in the cathode chamber of MFC for testing, using the same method as above.

[0100] The degradation results of rare earth wastewater by FM-NL@CFM cathode membrane (Example 1), FM-NL@CFM-1 cathode membrane (Example 2), FM-NL@CFM-2 cathode membrane (Example 3), and PVDF@CFM cathode membrane (Comparative Example 1) are shown in Figure 2 , where the horizontal axis represents time in h, the vertical axis represents the effluent concentration and removal efficiency in mg / L and %, and the hollow symbols and solid symbols represent the concentration and removal efficiency of Y ions, respectively. Figure 2 It can be seen that the FM-NL@CFM cathode membrane of Example 1 of the present invention can effectively reduce the yttrium element, and the maximum yttrium removal rate is 99.54%, which basically achieves complete removal of yttrium. The maximum yttrium removal rates of the PVDF@CFM cathode membrane of Example 1 of the FM-NL@CFM-1 cathode membrane of Example 2 and the FM-NL@CFM-2 cathode membrane of Example 3 are 98.4%, 96.75%, and 97.70%, respectively. This is because the cathode membrane of Comparative Example 1 does not contain the Ni-CAT@LDH@MWCNT catalyst. Since the addition of Ni-CAT@LDH@MWCNT is a way to improve the catalytic activity of the cathode membrane, the addition of the catalyst provides more reduction sites for yttrium ions in the electrocatalytic reduction, which can improve the reduction efficiency of yttrium ions on the electrode surface. The absence of the catalyst results in a lower redox activity, and the electrochemical performance of the cathode fails to be improved, thereby affecting the electrocatalytic activity of the MFC.

[0101] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a FM-NL@CFM cathode membrane, characterized in that: Using dimethylformamide as solvent, polyvinyl pyrrolidone as pore-forming agent, and polyvinylidene fluoride as binder, the Ni-CAT@LDH@MWCNT catalyst and substrate are combined, and then cured by phase inversion method to form a membrane, and then immersed in dilute hydrochloric acid solution and potassium permanganate solution to prepare the FM-NL@CFM cathode membrane; The Ni-CAT@LDH@MWCNT catalyst is prepared by mixing 2,3,6,7,10,11-hexahydroxytriphenyl, nickel acetate and LDH@MWCNT and subjecting the mixture to a hydrothermal reaction.

2. The method for preparing the FM-NL@CFM cathode membrane according to claim 1, characterized in that: The following steps are involved: Dimethylformamide, polyvinyl pyrrolidone, polyvinylidene fluoride and Ni-CAT@LDH@MWCNT catalyst were mixed and stirred, and reduced iron powder was added, mixed evenly, and degassed to obtain FM-NL@CFM cathode membrane casting solution; The FM-NL@CFM cathode membrane casting liquid is coated on a substrate, and after the membrane is formed, it is placed in a dilute hydrochloric acid solution for reaction, and then immersed in a potassium permanganate solution, and then washed and dried to obtain the FM-NL@CFM cathode membrane.

3. The method for preparing the FM-NL@CFM cathode membrane according to claim 2, characterized in that: In the FM-NL@CFM cathode membrane casting solution, the concentration of polyvinyl pyrrolidone is 2wt.%, the concentration of polyvinylidene fluoride is 10wt.%, the concentration of Ni-CAT@LDH@MWCNT catalyst is 0wt.%~1.8wt.%, and the concentration of reduced iron powder is 0wt.%~4wt.%, wherein the concentrations of Ni-CAT@LDH@MWCNT catalyst and reduced iron powder are not zero.

4. The method for preparing the FM-NL@CFM cathode membrane according to claim 2, characterized in that: The concentration of the dilute hydrochloric acid solution is 2 wt.%; and / or The concentration of the potassium permanganate solution is 0.2 mol·L -1 .

5. The method for preparing the FM-NL@CFM cathode membrane according to claim 2, characterized in that: The substrate is a carbon fiber material; and / or The soaking time is 12 hours; and / or The coating thickness was 300 μm.

6. The method for preparing the FM-NL@CFM cathode membrane according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120° C. and the time is 12 h.

7. The method for preparing the FM-NL@CFM cathode membrane according to claim 1, characterized in that: The mass ratio of the 2,3,6,7,10,11-hexahydroxytriphenyl, nickel acetate and LDH@MWCN is 7:14:

10.

8. A FM-NL@CFM cathode membrane, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. A microbial fuel cell, characterized in that: The FM-NL@CFM cathode membrane described in claim 8 is used as the cathode catalytic electrode.

10. Use of the FM-NL@CFM cathode membrane according to claim 8 or the microbial fuel cell according to claim 9 in treating rare earth wastewater.

Citation Information

Patent Citations

  • N-CNT-coated Fe-Mo catalyst and preparation method and application thereof

    CN116014154A

  • Manufacturing method of cathode of microbial fuel cell and cathode of microbial fuel cell manufactured by the same

    KR1020150067975A